2002
DOI: 10.1108/00070700210425778
|View full text |Cite
|
Sign up to set email alerts
|

Irish consumer preference for organic meat

Abstract: The consumer of today places increased importance on food safety, environmental and health issues and quality, hence some are willing to purchase organic meat. Evaluation models used in previous organic food research have identified variables such as health consciousness, environmental concern, animal welfare and income as important determinants of organic food choice. The objective of this research was to examine Irish consumer perceptions of organic meat. A questionnaire was completed by 250 respondents, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
116
6
8

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(147 citation statements)
references
References 9 publications
17
116
6
8
Order By: Relevance
“…While elderly consumers may purchase organic meat to gain a more healthy meal, younger consumers emphasize the importance of protecting the environment. O'Donovan and McCarthy (2002) found that consumers were more concerned about their health, rather than the environment or concerns about pollution when purchasing organic meat. McEachern and Schroder (2002) demonstrated similar results, reporting that consumers main motivation for buying organic food was concern about food safety, followed by concerns for animal welfare and finally the environment.…”
Section: The Food Has Been Produced In a Way That Is Good For The Envmentioning
confidence: 99%
“…While elderly consumers may purchase organic meat to gain a more healthy meal, younger consumers emphasize the importance of protecting the environment. O'Donovan and McCarthy (2002) found that consumers were more concerned about their health, rather than the environment or concerns about pollution when purchasing organic meat. McEachern and Schroder (2002) demonstrated similar results, reporting that consumers main motivation for buying organic food was concern about food safety, followed by concerns for animal welfare and finally the environment.…”
Section: The Food Has Been Produced In a Way That Is Good For The Envmentioning
confidence: 99%
“…Also consumers that are more concerned about the general importance of health, environment and animal welfare when purchasing food are expected to have larger organic budget shares (Hugner et al, 2007). But even though people may be concerned about the environment, health and animal welfare consequences of the food they buy, they do not necessarily behave in correspondence with this because organic consumption is, just as purchases of conventional food, influenced by general attitudes generated by socio-demographic status (Hughner, McDonagh, Prothero, Shultz, & Stanton, 2007;Smith, Huang, & Lin, 2009;Wandel & Bugge, 1997;O'Donovan & McCarthy, 2002;Sandalidou, Baourkis, & Siskos, 2002;Dettmann & Dimitri, 2010). …”
Section: Theoretical Modelmentioning
confidence: 99%
“…Previous research on organic consumers suggests that a relationship exists between socioeconomic characteristics of consumers and their likelihood of buying organic food (Dettmann & Dimitri, 2010;Fotopoulos & Krystallis, 2002;Krystallis et al 2006;Magnusson et al, 2001;O'Donovan & McCarthy, 2002;Zepeda & Li 2007). We investigate whether availability of organic food follows the same patterns, regarding socioeconomic characteristics, as the likelihood of buying organic food.…”
Section: Socioeconomic Characteristics and Organic Food Availabilitymentioning
confidence: 99%
“…GIS methods are widely used to examine issues related to food availability and access (see for example, Ghirardelli, Quinn, & Foerster, 2010;Kirkpatrick & Tarasuk, 2010;Rose, Bodor, & Rice, 2011). The choice of demographic characteristics mapped follows from the literature on organic food consumers, which finds that, after accounting for income and other factors, consumers with higher levels of education are more willing or likely to purchase organic products (Dettmann & Dimitri, 2010;Fotopoulos & Krystallis, 2002;Krystallis, Fotopoulos, & Zotos, 2006;Magnusson, Arvola, Koivisto Hursti, & Åberg, 2001;O'Donovan & McCarthy, 2002;Zepeda & Li, 2007). Research has yielded conflicting results on the impact of income and race on the likelihood of buying organic food (Durham, 2007;Govindasamy & Italia, 1990;Loureiro, McCluskey, & Mittlehammer, 2001).…”
mentioning
confidence: 99%